2007
DOI: 10.1016/j.jmb.2007.09.064
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Transcriptional Regulator AcrR from Escherichia coli

Abstract: The AcrAB multidrug efflux pump, which belongs to the resistance nodulation division (RND) family, recognizes and extrudes a wide range of antibiotics and chemotherapeutic agents and causes the intrinsic antibiotic resistance in Escherichia coli. The expression of AcrAB is controlled by the transcriptional regulator AcrR, whose open reading frame is located 141 bp upstream of the acrAB operon. To understand the structural basis of AcrR regulation, we have determined the crystal structure of AcrR to 2.55-A reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
91
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 77 publications
(98 citation statements)
references
References 47 publications
6
91
0
Order By: Relevance
“…The 35 nM affinity of CifR for the cifR proximal binding site is consistent with other TetR-family proteins, such as AcrR (20.2 nM) and CmeR (88 nM) in their affinity for their binding sites (23,35). The apparent dissociation constant for the morB proximal site is higher than that of the cifR proximal site, which may be attributable to differences in the sequences in these sites ( Fig.…”
Section: Discussionsupporting
confidence: 84%
“…The 35 nM affinity of CifR for the cifR proximal binding site is consistent with other TetR-family proteins, such as AcrR (20.2 nM) and CmeR (88 nM) in their affinity for their binding sites (23,35). The apparent dissociation constant for the morB proximal site is higher than that of the cifR proximal site, which may be attributable to differences in the sequences in these sites ( Fig.…”
Section: Discussionsupporting
confidence: 84%
“…8). Such a phenomenon has been previously observed with the crystal structure of QacR simultaneously bound to two ligands, proflavin and ethidium, 19 and has been predicted through biochemical analysis to occur in many other proteins, including AcrR, 22,23 TtgV 24 and MdfA. 25 It has also been reported that the QacR repressor can bind a single ligand in multiple positions, 26 possibly due to the multifaceted nature of this protein.…”
Section: Discussionmentioning
confidence: 61%
“…16 This is evident through protein sequence alignment that residues 7-60 of Rv1219c possess 25%, 24%, and 31% amino acid identity to TetR, 17 QacR, 18 and Rv3066, 14 respectively. In addition, superimposition of the Ca atoms of this N-terminal region, between residues 7 and 60, with those of AcrR 19 and Rv3066 14 results in overall rms deviations of 3.1 and 3.2 Å .…”
Section: N-terminal Domainmentioning
confidence: 97%
“…The corresponding distances between the two recognition helices of the DNAbinding domains are 35,39, and 42 Å in the apo forms of TetR, 17 QacR, 18 and AcrR. 19 Given that the separation between two successive major grooves of a B-form DNA is 34 Å , the large center-to-center distance of Rv1219c may allow this regulator to span three consecutive major grooves of the promoter DNA.…”
Section: N-terminal Domainmentioning
confidence: 99%
See 1 more Smart Citation